Impact of Long-Distance Travel on Rhegmatogenous Retinal Detachment Presentation and Outcome in Rural North Dakota. (July 2019) - Jacobs, David; Gokey, Robert; Beal, James R.
Purpose: Long-distance travel in underserved, rural areas could delay treatment of rhegmatogenous retinal detachment (RRD). The purpose of this study was to determine whether patients living remotely experienced a delay in treatment, presented with more-advanced RRD, or had worse visual acuity (VA) outcomes than patients living locally. Methods: A retrospective consecutive case series is presented of patients undergoing RRD repair by pars plana vitrectomy or scleral buckle from August 2011 to September 2014 in Minot, North Dakota, USA. Exclusion criteria were RRD cases presenting with concurrent vitreoretinal disease. Results: Of the 143 total patients, 45 lived locally, 5.2±1.6 miles (8.4±2.6 km), and 98 lived remotely, 122.8±69 miles (197.6±111 km). Duration of symptoms was 14.0±30.2 days for local and 19.2±37.5 days for remote patients ( P = .42). Time from referring provider exam to vitreoretinal surgeon exam was similar for local and remote patients, 1.5±2.9 vs 1.5±2.8 days ( P = .97). The fovea was detached in 51.1% of local and 53.6% of remote patients ( P = .78). Mean clock-hours of RRD were similar in local and remote patients, 5.2±2.3 vs 5.5±2.6 hours ( P = .51). Proliferative vitreoretinopathy was present in 6.7% of local vs 14.4% of remote patients ( P = .19). Time from vitreoretinal surgeon exam to surgical repair was similar for local and remote patients, 1.8±3.4 vs 1.8±3.8 days ( P = .70). The mean logMAR VA change at 6 months was similar in local and remote patients, –0.54±.7 vs –0.52±.8 ( P = .91). Reoperation was required in 4.4% of local vs 6.1% of remote patients ( P = .69). Conclusions: Patients traveling long distances for management of RRD did not experience a significant delay in treatment, present with more-advanced RRD, or have worse VA outcomes than patients who lived locally. Patients with RRD living in remote rural areas can have similar outcomes to patients living locally when referred and treated urgently.